You are on page 1of 2

# CHIP THICKNESS RATIO: - During the cutting action of a metal it will be observed

that t the thickness of the deformed or upward flowing chip is more to than the actual
depth of cut. It is because the chip flows upward at a slower rate than the velocity of the
cut. The velocity of the chip flow is directly effected by the shear plane angle .The
smaller this angle slower will be the chip flow velocity and, therefore, large will be the
thickness of the chip.

Figure 5.13 an orthogonal cutting operation
t1 = chip thickness prior to deformation
t2 = chip thickness after deformation.
The above discussion leads to the result that t2>t1.
The chip thickness ratio `r is given by:

r = t1/t2.

Since t2 always greater than t1, the value of chip thickness ratio `r is less than unity. The
higher the value of `r the better is supposed to be the cutting action. The reverse of `r is
known as chip reduction coefficient. If `k is the chip reduction coefficient, then:

K = 1/r

Now in orthogonal cutting the width of the chip equals to the width of the cut.
Considering the specific gravity of the metal as constant, the volume of the chip produced
will be equal to the volume of the metal cut. Widths of both being equal, the product of
the chip thickness and its length will therefore, be equal to the product to the thickness
and the length of the metal cut. If L1, L2 are the lengths of the metal cut and the chip
respectively, it follows that:

t1.L1 = t2.L2
i.e. t1/t2 = L2/L1
But t1/t2 = r
r = t1/t2 = L2/L1

In the given fig we have to right angled triangles OAP & OBP.considering the
right angle triangle OAP we have:

AP/OP = sin (AOP) =sin ()
So OP = AP/sin but (AP = t1)
So OP = t1/sin

Now considering the right angled triangle OBP we have

BP/OP = sin BOP = sin (90- + )
= cos ( - )

So OP = BP/cos ( - ) but (BP =t2)
So OP =t2/cos ( - )

Now by equating the equations for OP we get

t1 / sin = t2 / cos ( - ) T

or t1/t2 = sin() / cos( - ) = r

so r = sin() / cos( - )

the above can be expanded as

r = sin / (cos . cos + sin .sin)

r (cos.cos) + r (sin .sin )=sin .

r (cos .cos )/sin() + r(sin .sin )/sin = 1

So r cos /tan + r sin = 1

r cos /tan = 1 - r sin .

tan = r cos / 1 - r sin

also,by substituting the value of 'r' in terms of t1 & t2.we get

tan =((t1/t2) cos )/(1 -t1/t2 sin )